Evolution of Serial Patterns in the Vertebrate Pharyngeal Apparatus and Paired Appendages via Assimilation of Dissimilar Units - Miyashita, Tetsuto; Diogo, Rui (Frontiers in Ecology and Evolution, 2016)
Evolution of serially similar structures has attracted interest since the infancy of comparative morphology and embryology. A long-standing assumption is that the serial patterning reflects ancestral metamerism, which persists in preconceived character polarity from a primitive state of polyisomerism (a series of identical or similar units) to a derived state of anisomerism (a series of differentially specialized parts). We test this assumption against an alternative character polarity — from anisomeric to polyisomeric — in the vertebrate pharyngeal apparatus and paired appendages. We show that, contrary to what is usually assumed, serial similarity represents a derived state in both pharyngeal apparatus and paired appendages: the distinctly patterned structures secondarily assimilated each other. Acquisitions of serial similarity in the pharyngeal apparatus and paired appendages straddle major evolutionary events such as the origin of the jaw and fish-tetrapod transitions. We suggest that: (a) the origin of the jaw coincided with extension of the serial pharyngeal patterning onto the mandibular region; and (b) the pectoral and pelvic appendages have independent origins and their distal portions acquired serial similarities later during the fin-limb transitions.